2020
DOI: 10.1007/s42804-020-00080-8
|View full text |Cite
|
Sign up to set email alerts
|

Is the lower pole crossing vessels transposition a valid option for the treatment of extrinsic ureteropelvic obstruction in children? Considerations from a single-centre experience

Abstract: Objective To assess the efficacy of the vascular hitch procedure in extrinsic ureteropelvic junction obstruction (UPJO) by crossing vessels in children, both by open and mini-invasive approach. Methods Retrospective analysis on patients treated by open or mini-invasive vascular hitch during the period 2006-2020. Preoperative imaging included renal ultrasound (US) and functional studies by magnetic resonance or renogram. Crossing vessels obstruction and UPJ anatomy were evaluated at surgery. Success was defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Menon et al identified radiological findings on MRU suspicious for the presence of CV (small, intrarenal, globular pelvis, widening of the pyelo-calyceal junction, and prominent calyceal dilation) ( 38 ). Fiorenza et al found that fMRU was helpful to identify CV in 89.2% of cases ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Menon et al identified radiological findings on MRU suspicious for the presence of CV (small, intrarenal, globular pelvis, widening of the pyelo-calyceal junction, and prominent calyceal dilation) ( 38 ). Fiorenza et al found that fMRU was helpful to identify CV in 89.2% of cases ( 39 ).…”
Section: Discussionmentioning
confidence: 99%